Dendrogeomorphic reconstruction of flash floods in the Patagonian Andes - Casteller, Alejandro; Stoffel, Markus; Crespo, Sebastián Andrés; Villalba, Ricardo; Corona, Christophe; Bianchi, Emilio (Elsevier, 2019)
Flash floods represent a significant natural hazard in small mountainous catchments of the Patagonian Andes and have repeatedly caused loss to life and infrastructure. At the same time, however, documentary records of past events remain fairly scarce and highly fragmentary in most cases. In this study, we therefore reconstruct the spatiotemporal patterns of past flash flood activity along the Los Cipreses torrent (Neuquén, Argentina) using dendrogeomorphic methods. Based on samples from Austrocedrus chilensis, Pseudotsuga menziesii, and Nothofagus dombeyi, we document 21 flash flood events covering the period A.D. 1890–2009 and reconstruct mean recurrence intervals of events at the level of individual trees being impacted, which varies from 4 to 93 years. Results show that trees tend to be older (younger) in sectors of the torrent with gentler (steeper) slope gradients. Potential triggers of flash floods were analyzed using daily temperature and precipitation data from a nearby weather station. Weather conditions leading to flash floods are abundant precipitations during one to three consecutive days, combined with temperatures above the rain/snow threshold (2 °C) in the whole watershed.